Consumo de drogas no contexto da privação de liberdade de adolescentes no município de Ponta Grossa: demandas e desafios da atenção em saúde. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This study has as its object the comprehensive health care of adolescents in conflict with the law in compliance with socio-educational measures deprived of freedom with health demands related to drug use in the municipality of Ponta Grossa. This discussion becomes necessary and relevant due to the novelty of the proposal, the lack of research on this topic and the intensification of social policies today. In this sense, the present research deals especially with the comprehensive health care of adolescents in conflict with the law while serving a socio-educational measure depriving them of freedom. Its general objective is to analyze how the access to analytical services by adolescent drug users occurs in the context of the execution of the deprivation of freedom socioeducational measure and how they are treated by the socioeducational policy in the municipality of Ponta Grossa - PR. This is an interdisciplinary, qualitative, and exploratory research. To this end, initially, a bibliographic and documental research was carried out, and in a second moment, a field research. The research universe is configured by the Centro de Socioeducação Regional de Ponta Grossa, and the research sample is formed by members of the technical team, health team and managers of the institution. As a data instrument, a data form and a semi-structured interview script were used. Finally, content analysis was used to analyze the data collected. The chapter that opens this research aims, in a first moment, to conceptually situate the emergence of the bourgeoisie and its domination process, the formation of the capitalist state and the subordinate condition of the working class, the origin and development of the social issue, and social policy in monopoly capitalism. In a second moment, it discusses human development in the capitalist order from a pluralist theoretical anchorage, making a critique of the way the capitalist system interferes in human development. Chapter 2 presents, in a first moment, the concept of adolescence as a historical and social construction, discusses how the use of drugs has acquired different functions from those previously seen in the historical process of humanity, discusses drug use in adolescence correlating it with the concepts of social vulnerability and subalternity. Next, it discusses the deprivation of freedom of adolescents and drug use as a health issue, presenting the legal aspects and the guidelines for action in the scope of health care in social education and health care in the face of the issue of drug use in the context of the deprivation of freedom socio-educational measure. Finally, the third chapter, of an empirical nature, indicates the categorization of the data collected from the data forms and interviews conducted with the research subjects, using the bio-ecological theory of development as the theoretical basis for sustaining the analysis. The main results indicate that there is a low quality of interaction between the Regional Social Education Center of Ponta Grossa and the municipal care network, which hinders the access of adolescents who have health demands related to drug use in the health services of the network.
Keywords: Consumo de drogas; Vulnerabilidade Social na Adolescência; Atenção em Saúde; Medida Privativa de Liberdade; Política Pública de Socioeducação.; Drug Use.; Social Vulnerability in Adolescence; Health Care; Deprivation of Liberty Measure; Socioeducation Public Policy; CNPQ::CIENCIAS SOCIAIS APLICADAS